Efforts To Improve Understanding Of The Concept Of Composite Reduction Using Digital Scratch Media With The CRT Approach - Sinuraya, Putri Yohana M.; Ammy, Putri Maisyarah; Harianty, Shofya S (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to improve the understanding of the concept of compound subtraction through Scratch media with the Culturally Responsive Teaching (CRT) approach in grade II students of SD Negeri 066055 Medan Denai. This study is a Classroom Action Research (CAR) with the Kemmis, McTaggart, and Nixon model which is implemented in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The research subjects were 15 students, consisting of 8 boys and 7 girls. Data were collected through pretest and posttest tests to measure the ability to understand mathematical concepts, as well as documentation to support the learning process. The results of the study showed that in cycle I, students who completed the learning only reached 40% or 6 out of 15 students. After learning improvements were made in cycle II, there was a significant increase, namely as many as 13 out of 15 students (86.67%) reached the specified Minimum Completion Criteria (KKM), which is ≥70. These results indicate that the use of Scratch media combined with the CRT approach is able to improve students' understanding of the concept of compound subtraction. This approach allows students to learn in a way that is more contextual, engaging, and appropriate to their cultural background.